Reading medieval ruins urban life and destruction in sixteenth-century Japan - Pitelka, Morgan 1972- (Cambridge University Press, 2022)
The Japanese provincial city of Ichijōdani was destroyed in the civil wars of the late sixteenth century but never rebuilt. Archaeological excavations have since uncovered the most detailed late medieval urban site in the country. Drawing on analysis of specific excavated objects and decades of archaeological evidence to study daily life in Ichijōdani, Reading Medieval Ruins in Sixteenth-Century Japan illuminates the city's layout, the possessions and houses of its residents, its politics and experience of war, and religious and cultural networks. Morgan Pitelka demonstrates how provincial centers could be dynamic and vibrant nodes of industrial, cultural, economic, and political entrepreneurship and sophistication. In this study a new and vital understanding of late medieval society is revealed, one in which Ichijôdani played a central role in the vibrant age of Japan's sixteenth century
Title from publisher's bibliographic system (viewed on 01 Apr 2022)
A Provincial Palace City as an Urban Space -- The Material Culture of Urban Life -- Late Medieval Warlords and the Agglomeration of Power -- The Material Foundations of Faith -- Culture and Sociability in the Provinces -- Urban Destruction in Late Medieval Japan -- Epilogue - The Excavated Nation on Display
Keywords: Asakura family; Ichijōdani (Japan) / History; Ichijōdani (Japan) / Social life and customs; Fukui-ken (Japan) / History / 16th Century